Genomic studies on Strongyloides stercoralis in northern and western Thailand - Kittipat Aupalee (2020)
© 2020 The Author(s). Background: Strongyloidiasis is a soil borne helminthiasis, which in most cases is caused by Strongyloides stercoralis. Human infections with S. fuelleborni fuelleborni and S. fuelleborni kellyi also occur. Although up to 370 million people are currently estimated to be infected with S. stercoralis, this parasite is frequently overlooked. Strongyloides stercoralis is prevalent among humans in Thailand; however, S. fuelleborni fuelleborni has also been reported. Three recent genomic studies of individual S. stercoralis worms found genetically diverse populations of S. stercoralis, with comparably low heterozygosity in Cambodia and Myanmar, and less diverse populations with high heterozygosity in Japan and southern China that presumably reproduce asexually. Methods: We isolated individual Strongyloides spp. from different localities in northern and western Thailand and determined their nuclear small ribosomal subunit rDNA (18S rDNA, SSU), in particular the hypervariable regions I and IV (HVR-I and HVR-IV), mitochondrial cytochrome c oxidase subunit 1 (cox1) and for a subset whole genome sequences. These sequences were then compared with each other and with published sequences from different geographical locations. Results: All 237 worms isolated from 16 different human hosts were S. stercoralis, no S. fuelleborni was found. All worms had the common S. stercoralis SSU HVR IV haplotype A. Two different SSU HVR I haplotypes (I and II), both previously described in S. stercoralis, were found. No animal heterozygous for the two haplotypes was identified. Among the twelve cox1 haplotypes found, five had not been previously described. Based upon the mitochondrial cox1 and the nuclear whole genome sequences, S. stercoralis in Thailand was phylogenetically intermixed with the samples from other Southeast Asian countries and did not form its own branch. The genomic heterozygosity was even slightly lower than in the samples from the neighboring countries. Conclusions: In our sample from humans, all Strongyloides spp. were S. stercoralis. The S. stercoralis from northern and western Thailand appear to be part of a diverse, intermixing continental Southeast Asian population. No obvious indication for genetic sub-structuring of S. stercoralis within Thailand or within the Southeast Asian peninsula was detected.[Figure not available: see fulltext.].